«Machen Sie mich nicht reich. Geben Sie mir nur so viel, als man braucht, wenn man nicht gehorchen, und nicht befehlen will». Strategie del possesso nella «Betschwester» di Christian Fürchtegott Gellert: [«Do not make me rich. Give me only so much as one needs when one does not want either to obey or to command». Strategies of possession in Christian Fürchtegott Gellert’s «The Prayer Sister»] (Studia theodisca, 2020)
As in all Gellert’s comedies, the characters of the The Prayer Sister (1745) aspire to both material well-being and an ideal spiritual happiness. The impulse to possession, which encompasses the sphere of reality as well as that of the symbolic, is an ambivalent, contradictory force. The aim of self-affirmation through wealth is coherent with bourgeois dynamism. The consequent exposure to the loss of a moral compass, however, corresponds to a drainage of the vital force which impels the logic of wish. This study deals with these themes both in Gellert’s theatre and in his essays.